Fluid deresuscitation in critically ill children: comparing perspectives of intensivists and nephrologists - Braun, Chloe G.; Askenazi, David J.; Neyra, Javier A.; Prabhakaran, Priya; Rahman, A. K. M. Fazlur; Webb, Tennille N.; Odum, James D. (Frontiers in Pediatrics, 2024)
Introduction: Fluid accumulation, presently defined as a pathologic state of overhydration/volume overload associated with clinical impact, is common and associated with worse outcomes. At times, deresuscitation, the active removal of fluid via diuretics or ultrafiltration, is necessary. There is no consensus regarding deresuscitation in children admitted to the pediatric intensive care unit. Little is known regarding perceptions and practices among pediatric intensivists and nephrologists regarding fluid provision and deresuscitation. Methods: Cross-sectional electronic survey of pediatric nephrologists and intensivists from academic societies in the United States designed to better understand fluid management between disciplines. A clinical vignette was used to characterize the perceptions of optimal timing and method of deresuscitation initiation at four timepoints that correspond to different stages of shock. Results: In total, 179 respondents (140 intensivists, 39 nephrologists) completed the survey. Most 75.4% (135/179) providers believe discussing fluid balance and initiating fluid deresuscitation in pediatric intensive care unit (PICU) patients is “very important”. The first clinical vignette time point (corresponding to resuscitation phase of early shock) had the most dissimilarity between intensivists and nephrologists (p=0.01) with regards to initiation of deresuscitation. However, providers demonstrated increasing agreement in their responses to initiate deresuscitation as the clinical vignette progressed. Compared to intensivists, nephrologists were more likely to choose “dialysis or ultrafiltration” as a deresuscitation method during the optimization (10.3 vs 2.9% [p=0.07]), stabilization (18.0% vs. 3.6% [p<0.01]), and evacuation (48.7% vs. 23.6% [p<0.01]) phases of shock. Conversely, intensivists were more likely to utilize scheduled diuretics than nephrologists (47.1% vs 28.2% [p=0.04]) later on in the patient course. Discussion: Most physicians believe that discussing fluid balance and deresuscitation is important. Nevertheless, when to initiate deresuscitation and how to accomplish it differed between nephrologist and intensivists. Widely understood and operationalizable definitions, further research, and eventually evidence-based guidelines are needed to help guide care.